Association between endothelial nitric oxide synthase intron 4a/b polymorphism and aortic dissection - Ahmet Ekmekçi; Mahmut Uluganyan; Barış Güngör; Neslihan Abacı; Kazım Serhan Özcan; Gokhan Ertaş; Aycan Zencirci; Ahmet Yavuz Balcı; Sema Sırma Ekmekçi; Nurten Sayar; Duran Ustek; Mehmet Eren (KARE Publishing, 2014)
Objectives: The genetic risk factors that contribute to the risk of developing aortic dissection (AD) have been studied. We assessed the association of endothelial nitric oxide synthase (eNOS) gene polymorphism with AD. Study design: Patients who underwent surgery with the diagnosis of AD and survived after the operation in our center between May 2007 and June 2011 were recruited retrospectively. The eNOS intron 4a/b polymorphism was determined by polymerase chain reaction (PCR) using oligonucleotide primers (sense: 5'-AGGCCCTATGGTAGTGCCTTT-3'; antisense: 5'-TCTCTTAGTGCTGTGGTCAC-3') that flank the region of the 27 bp VNTR in intron 4. Results: Thirty-nine patients (88%) had type A AD, while the remainder (12%) had type B AD. The distribution of eNOS4 a/b gene polymorphism differed significantly from the control group, with higher frequencies of eNOS 4a/a and 4a/b genotypes in the AD group (χ2=7.16, p=0.03). Conclusion: In this study, the distribution of eNOS genotypes differed between the AD and control groups; however, this polymorphism was not found to be an independent factor for the development of AD.